EFEKTIFITAS PENURUNAN Fe 2+ DENGAN UNIT SARINGAN PASIR CEPAT MEDIA PASIR AKTIF - Oktiawan, Wiharyanto; Krisbiantoro, Krisbiantoro (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
The process that happened in decreasing Fe2+ with a rapid sand filter are mechanical straining, sedimentation, adsorbs and an activities of chemical in the water it self. This research uses 2 stages in testing; they are the batch filter and the column filter. On each of the stages we try using activated sand media. This media is known to able to decrease the Fe2+. The water spring is from the 2nd deep well at the Prambanan water treatment facility. The goal from this research is to find the criteria design on surface loading and to find out the effectiveness in reducing Fe2+ that is in the water by using the media of activated sand. From this experiment we found that the maximal filtration speed on activated sand is 12, 85 m/jam. Calculation analysis shows that the removal  coefficient  of  Fe2+  in  the  batch activated  sand  filter  is  λ 1   =  0,92  ±  0,16  m-1  with  the average on reducing Fe2+ 42,27%.